Double pulse transmission - signal-to-noise ratio improvement in ultrasound imaging - TROTS, Ihor; NOWICKI, Andrzej; LEWANDOWSKI, Marcin; SECOMSKI, Wojciech; LITNIEWSKI, Jerzy (Archives of Acoustics, 2008)
This study investigates a new composing method of double transmission of short coded sequences based on well-known Golay complementary codes, which allow to obtain the higher signal-to-noise ratio (SNR) and increase penetration depth. The proposed method can potentially find application in small parts ultrasonography and play important role in examination of superficial structures, e.g. in dermatology, ophthalmology, etc., where using longer coded sequences leads to increase of a dead zone and single pulse transmission of short sequences does not assure sufficient SNR. This paper discusses the comparison of results obtained during the examination of four different lengths pairs of Golay coded sequences excited at 3.7 MHz: the single 64-bits pair of Golay sequences and combined sequences consisting of two 8-, 16-, and 32-bits Golay codes separated in time. The experimental results have shown that using the double pulse transmission allows to suppress considerably the noise level, the SNR increases by 5.7 dB in comparison with the single pulse transmission of Golay sequences of the same length. The results of this work indicate that double pulse transmission enhances SNR while maintaining the dead zone short.